CCDC22 and CCDC93, two potential retriever-interacting proteins, are required for root and root hair growth in Arabidopsis - Lewis, Connor D.; Preston, Jill C.; Tierney, Mary L. (Frontiers in Plant Science, 2022)
Endomembrane trafficking is essential for plant growth and often depends on a balance between secretory and endocytic pathways. VPS26C is a component of the Retriever complex which has been shown to function in the recycling of integral plasma membrane proteins in human cell culture and is part of a core retriever complex in Arabidopsis that is required for root hair growth. In this work, we report a characterization of the Arabidopsis homologues of CCDC22 and CCDC93, two additional proteins required for retriever function in humans. Phylogenetic analysis indicates that CCDC22 (AT1G55830) and CCDC93 (AT4G32560) are single copy genes in plants that are present across the angiosperms, but like VPS26C, are absent from the grasses. Both CCDC22 and CCDC93 are required for root and root hair growth in Arabidopsis and localize primarily to the cytoplasm in root epidermal cells. Previous work has demonstrated a genetic interaction between retriever function and a VTI13-dependent trafficking pathway to the vacuole. To further test this model, we characterized the vti13 ccdc93 double mutant and show that like vps26c, ccdc93 is a suppressor of the vti13 root hair phenotype. Together this work identifies two new proteins essential for root and root hair growth that likely function with the retriever complex in plants and demonstrate that the endosomal pathway(s) in which CCDC93 functions is genetically linked to a VTI13-dependent trafficking pathway to the vacuole.